E-COMMERCE ALAT TELEKOMUNIKASI CEK SINYAL TELEPON SELULER PT. NEXWAVE (Jurnal Dinamika Informatika, 2014)
In a system that is running there are many obstacles, among others, the difficulty of promoting goods PT. Nexwave to many customers. As for this offering and the transactions done manually that is only counting direct purchase namely buyer comes directly or by telephone to PT. Nexwave. While there are many limitations on customers who make customers less comfortable in the view, select and transact with a seller. PT. Nexwave'd crawl customers not just confined to one city or one county alone. By considering the various problems that exist and the great profits and benefits achieved through ecommerce Keywords – Information Systems, E-commerce, check cell phone signal